2001
DOI: 10.4269/ajtmh.2001.65.420
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of antibody responses to combinations of a dengue-2 DNA and dengue-2 recombinant subunit vaccine.

Abstract: Abstract. A dengue-2 (DEN-2) DNA vaccine coding for the premembrane and envelope (E) proteins and a recombinant fusion protein containing the B domain of the DEN-2 E protein fused to the maltose-binding protein (MBP) of Escherichia coli both elicited neutralizing antibody in mice. In order to achieve more rapid protective immunity as well as to increase the persistence of neutralizing antibody, we primed mice with the DNA vaccine (D), the recombinant MBP protein (R), or both (RD) given simultaneously, and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 35 publications
3
42
2
Order By: Relevance
“…Therefore, it is reasonable to suggest that VN antibody against PCV2 is composed mainly of IgG2a antibody against Cap protein, and that this Cap-specific neutralizing IgG2a antibody plays an important role in protecting against PCV2 infection. In fact, VN antibodies against dengue virus (Simmons et al, 2001) and herpes simplex virus type 1 (McKendall & Woo, 1988) have also been shown to comprise primarily IgG2a antibody in mice. A recent study reported that recombinant adenovirus expressing the Cap protein generated VN antibody titres ranging from 1 : 8 to 1 : 17 in mice (Wang et al, 2006), and all plasmids encoding Cap protein with different subcellular localizations induced VN antibody titres of ,1 : 10 in mice (Fan et al, 2008).…”
Section: Groupmentioning
confidence: 99%
“…Therefore, it is reasonable to suggest that VN antibody against PCV2 is composed mainly of IgG2a antibody against Cap protein, and that this Cap-specific neutralizing IgG2a antibody plays an important role in protecting against PCV2 infection. In fact, VN antibodies against dengue virus (Simmons et al, 2001) and herpes simplex virus type 1 (McKendall & Woo, 1988) have also been shown to comprise primarily IgG2a antibody in mice. A recent study reported that recombinant adenovirus expressing the Cap protein generated VN antibody titres ranging from 1 : 8 to 1 : 17 in mice (Wang et al, 2006), and all plasmids encoding Cap protein with different subcellular localizations induced VN antibody titres of ,1 : 10 in mice (Fan et al, 2008).…”
Section: Groupmentioning
confidence: 99%
“…A vaccine which achieves this is expected to provide uniform protection against all serotypes and a low risk of ADE. A variety of vaccine approaches have been undertaken, including empirically derived and cDNA-derived live attenuated viruses, recombinant subunit vaccines, inactivated virus, and DNA vaccines (2,3,5,13,19,20,24,25,28,31,32,45,47,48,(52)(53)(54). Although some candidates have progressed to clinical trials, there have been problems with immunogenicity and reactogenicity of certain vaccines, and it is not yet known which modality will be most suitable for use in humans.…”
mentioning
confidence: 99%
“…Another molecular approach being utilized is the creation of four separate infectious chimeric flaviviruses, each of which contains the pre-M and E genes of one of the four DENV serotypes in a single "backbone" containing the C and NS proteins of an attenuated flavivirus, either the yellow fever vaccine strain or an attenuated DENV strain (21,22). DNA vaccines consisting of plasmids expressing one or a few proteins from each DENV serotype are in an earlier stage of development, as are subunit vaccines based on purified recombinant DENV proteins (23,24). Several of these approaches have demonstrated protective efficacy in animal models of DENV infection, and a few have shown safety and immunogenicity in early phase clinical studies (14,18,25,26).…”
mentioning
confidence: 99%